2008
DOI: 10.1002/ana.21403
|View full text |Cite
|
Sign up to set email alerts
|

Ambient air pollution and risk for ischemic stroke and transient ischemic attack

Abstract: Background Data on the association between air pollution and cerebrovascular disease in the US are limited. The objective of this study was to investigate the association between short-term exposure to ambient air pollution and risk of ischemic cerebrovascular events in a US community. Methods Daily counts of ischemic strokes/TIAs (2001–2005) were obtained from the population-based Brain Attack Surveillance in Corpus Christi (BASIC) Project. Daily particulate matter <2.5μm in diameter (PM2.5), ozone (O3), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
127
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 144 publications
(143 citation statements)
references
References 38 publications
11
127
5
Order By: Relevance
“…Specific cardiovascular events considered to be associated with air pollution include ischemic heart disease, 1 heart failure, 2 cardiac arrhythmia/arrest, 3 and ischemic stroke. 4 However, the findings for hemorrhagic stroke remain inconsistent. Most such studies in Western countries have linked the levels of air pollutants to ischemic but not hemorrhagic stroke.…”
mentioning
confidence: 99%
“…Specific cardiovascular events considered to be associated with air pollution include ischemic heart disease, 1 heart failure, 2 cardiac arrhythmia/arrest, 3 and ischemic stroke. 4 However, the findings for hemorrhagic stroke remain inconsistent. Most such studies in Western countries have linked the levels of air pollutants to ischemic but not hemorrhagic stroke.…”
mentioning
confidence: 99%
“…1 Several studies have examined the acute effects of outdoor air pollution on stroke using daily time series and case-crossover study designs. [2][3][4][5][6][7][8][9] Although a number of these studies have examined mortality and others have used hospital admissions as a proxy for incident cases, a few have used population case registers, which aim to capture all incident cases. 4,5 A number of these acute effects studies have reported associations between outdoor air pollutants and ischemic stoke, 4,6,7 whereas others have also reported associations with hemorrhagic stroke.…”
mentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9] Although a number of these studies have examined mortality and others have used hospital admissions as a proxy for incident cases, a few have used population case registers, which aim to capture all incident cases. 4,5 A number of these acute effects studies have reported associations between outdoor air pollutants and ischemic stoke, 4,6,7 whereas others have also reported associations with hemorrhagic stroke. 8,9 In contrast, although there is an increasing number of studies examining the effects of chronic exposure to outdoor air pollution on cardiovascular mortality using cohort study designs, 10 few have specifically examined stroke mortality.…”
mentioning
confidence: 99%
“…We have identified 18 studies, which fulfilled these criteria (Table 4). [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] ACUTE EFFECTS OF PARTICULATE MATTER EXPOSURE Although most studies on PM and cardiovascular diseases have been conducted in developed western countries, first impulses for epidemiologic research on IS came from South Korea and Taiwan. 15,22,25 An increase in PM by an interquartile range in Seoul was associated with a 3% higher IS mortality.…”
Section: Particulate Matter and Human Health Particulate Matter Is A mentioning
confidence: 99%